제조물책임(製造物責任) 관리활동(管理活動)과 기업(企業) 가치(價値)간의 상관관계 및 대응전략(對應戰略) 연구 - 민동성; 장석주; 박노국 (벤처창업연구, 2008)
The manager of manufacturing industry just not to have known to do related to the law of Product Liability that was put into operation in July 2002. The law of PL is a public law about defective product, which was established in order to compensate consumer's damages of property and body caused by product, to make sound society by the safety products and to take international competitiveness. The economic effects by the law of Product Liability are the increase of consumers relief production cost by the lawsuits. Product liability as a process has developed significantly in the United Kingdom and the United States of America. The rapid introduction of product liability has recently been a prevalent phenomenon, as global changes arising from rapid development in science and the economy have resulted in a highly interconnected world economy. This thesis was established, based on current literature and business consulting cases in the position of companies, and is one of the operating subjects in a system for legal responsibility in manufactured products. However, there are limitations in the fact that research theories are only able to present a theoretical model and directions. In this context, managers and personnel of multiple companies cannot adequately respond to the recently enforced Product Liability Act. The major findings are summarized as Product Liability Management Activity are positively Correlation of Enterprise Value. 2002년 제조물책임법이 시행된 이후 정부에서는 종합시책을 확정하고, 업종별 PL센터를 설립하여 소비자 상담과 분쟁에 적극 대응하고 있다. 그러나 아직 많은 기업들이 제품고유의 안전성 확보를 위한 철학과 기술을 가지고 있지 못하여 제조물책임법에 대한 대응체계가 미흡한 것이 사실이다. 본 연구의 목적은 제조물책임 관련 안전사고와 리콜실태, 소비자 위해실태, Pl보험사고 소송사례 등을 실증적 사례중심으로 검토.분석하여 이를 토대로 제조물 책임이 기업 가치에 어떠한 영향을 미치는지 상호관계를 연구하고, 기업의 제조물책임 대응전략을 제시하는데 그 의미가 있다.